Earth plasters against weather: Adhesion-improvement strategies using natural materials (ARQUISUR Revista, 2023)
Earth construction technologies are outstanding for their alignment with environmental sustainability. Earth plasters are essential in this type of construction, providing protection against exposure to open sky.  However, in light earth walls (LEM, Light Earth Method), where parts of the structural timber are exposed, some challenges affect the adhesion of plaster. This can lead to cracking and detachment, threatening the structure's durability against environmental factors. This research work assessed the adhesion of plasters on LEM walls, considering rain, wind, solar radiation, and the orientation and type of protective paint. The work proposes the use of bonding layers of natural material before thick plasters on areas of exposed wood and samples must be subjected to pull-out tests after two rainy periods of time. The results support the effectiveness of natural materials as plasters and protectors for light earth walls. The choice between natural or synthetic paint does not significantly affect adhesion during the evaluated period. However, dry preparation of samples for pull-out testing reduced adhesion and generated unfocused data.
Keywords: sustainable architecture; experimental construction; materials testing; coatings; mixed technique